Exploring the roles of fear and powerlessness in the relationship between perceived risk of the COVID-19 pandemic and information-avoidance behavior - Zhang, Kunying; Zhang, Naifu; Wang, Jie; Jiang, Jie; Xu, Sihua (Frontiers in Psychology, 2022)
The current investigation was conducted to determine the correlation between the perceived epidemic risk of coronavirus disease 2019 (COVID-19) and information-avoidance behavior and the mediating role of fear and powerlessness during the COVID-19 pandemic in China. Structural equation modeling (SEM) was performed to test the conceptual model, where the perceived risk of the COVID-19 pandemic was considered a predictor, fear and powerlessness as mediating variables, and information-avoidance behavior as the outcome. A total of 557 Chinese respondents with COVID-19 treated in modular hospitals were recruited and completed a questionnaire containing scales of the perceived epidemic risk of COVID-19, fear, powerlessness, and information-avoidance behavior. The results yielded from the Structural equation modeling analysis indicated a significant and positive association between the perceived epidemic risk of COVID-19 and information-avoidance behaviors. Powerlessness acted as the mediator between the perceived epidemic risk of COVID-19 and information-avoidance behavior. The perceived epidemic risk of COVID-19 influenced information-avoidance behavior through feelings of fear and powerlessness in turn. These results provide a more comprehensive understanding of why and how the perceived epidemic risk of COVID-19 predicts information-avoidance behavior.